Peran Penghulu dalam Meningkatkan Kualitas Pelayanan Nikah Rujuk - Zubir, Muhammad (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes that the Office of Religious Affairs (KUA) is a work unit of the Ministry of Religion at the District level in serving the needs of the community. One of the 10 most important tasks and functions of the KUA is: "organizing the process of recording marriage contracts". In this case, the position of the headman plays an important role in the context of the success and running of government programs related to the issue of marriage registration so that they can run well and optimally. For this reason, a penghulu is required to always be active and creative in providing services to the public in a professional manner, with the principles of humanity and justice. Furthermore, the task of the prince in improving service and improving the quality of the family is to provide marriage/referral consultation services through Pre-Marriage coaching to prospective brides and grooms which are carried out in accordance with the conditions of each region, in an effort to comply with applicable regulations in the field of NR services. Therefore, the formulation of this paper is how far the prince's efforts are in improving the quality of Marriage and Reconciliation services and how the performance and professionalism of the prince as an expert and professional position. The aim is to find out how far the prince's efforts are in improving the quality of marriage and reconciliation services and to find out the Performance and Professionalism of the Penghulu as an expert and professional position.